A prospective case series evaluating efficacy and safety of combination of itraconazole and potassium iodide in rhinofacial conidiobolomycosis. (31st July 2015) - Gupta, Manish; Narang, Tarun; Kaur, Rupinder Jeet; Manhas, Ashwani; Saikia, Uma Nahar; Dogra, Sunil
Abstract: Background: Rhinofacial conidiobolomycosis (RFC) is an uncommon subcutaneous fungal infection producing painless swelling with grotesque deformity of the face. Although there are case reports and small case series; there are very few prospective studies evaluating treatment outcome and long‐term follow‐up. Objective: To evaluate the safety and efficacy of combination of itraconazole (200 mg twice daily) and saturated solution of potassium iodide (SSKI) in patients with RFC. Methods: Ten patients of RFC were studied over a period of 5 years. Diagnosis was confirmed by clinical, histopathological, and microbiological evaluation. Conidiobolus was cultured in four cases and in the rest of the cases, the histopathology was suggestive of RFC. They were treated with itraconazole (200 mg twice daily) and SSKI and followed up for a minimum of 1 year after stopping treatment. Results: The mean age was 38.7 years and the mean duration of symptoms was 22.4 months. Males were predominantly involved (9 : 1). Seven patients responded to the combination treatment, five had complete resolution and two had good improvement (50–75%); however, in two patients the response was minimal (<25% regression of the swelling) and one patient did not show any improvement after 6 months of treatment. Conclusion: Combination of itraconazole and SSKI is an effective treatment modality for RFC with relatively faster onset of action, low relapse rates, and minimal adverse effects. It can be considered as first‐line treatment in patients with RFC.